RENAME AND RESIST COLONIAL EXTRACTION: TWITTER’S TOPONYMIC POLITICS - Karsgaard, Carrie; Hockenhull, Michael; MacDonald, Maggie (AoIR Selected Papers of Internet Research, 2020)
In Canada, known to Indigenous peoples as Turtle Island, the proposed Trans Mountain pipeline would more than double transport of bitumen from Alberta’s oil sands, and though national legitimation of the project is strong, it relies on economic discourse that overwrites environmental concerns, as well as Canada’s lack of consultation with Indigenous peoples. Rejecting settler-colonial authority, pipeline protestors have turned to on-the-ground tactics including petitions and demonstrations - and also to social media, where they share information, organize, and express resistance. On Twitter, user profiles are associated with a diversity of locations including places like Vancouver and Ottawa, recognized under “official,” colonial names. Twitter’s free-form location field, however, enables users to self-select their locations, and connect with one another by situating themselves according to anti-colonial or Indigenous place names, such as “Secwepemcul’ecw” and “Unceded Syilx Territory.” Considering the colonial nature of resource extraction in Canada (Preston, 2017), our project addresses: in what ways does anti-pipeline sentiment correlate with anti-colonial or Indigenous-affiliated toponymic identifiers on Twitter? Applying digital methods, we found empirically that these locations map onto the hashtag discursive space consistently with the issue alignment of discourses, suggesting that users on Twitter do indeed engage in toponymic politics (Rogers, 2015). As a space of resistance and expression of marginalized perspectives, Twitter’s free-form user location enables political expression in ways that unavailable on platforms insisting on geolocation or geotagging. By design, Twitter enables users to establish geographies of trust beyond colonial hegemony as users identify according to Indigenous place names.